Potential role of vitamin D deficiency on Fabry cardiomyopathy. Issue 2 (19th October 2013) - Drechsler, Christiane; Schmiedeke, Benjamin; Niemann, Markus; Schmiedeke, Daniel; Krämer, Johannes; Turkin, Irina; Blouin, Katja; Emmert, Andrea; Pilz, Stefan; Obermayer‐Pietsch, Barbara; Weidemann, Frank; Breunig, Frank; et al.
Abstract: Patients with Fabry disease frequently develop left ventricular (LV) hypertrophy and renal fibrosis. Due to heat intolerance and an inability to sweat, patients tend to avoid exposure to sunlight. We hypothesized that subsequent vitamin D deficiency may contribute to Fabry cardiomyopathy. This study investigated the vitamin D status and its association with LV mass and adverse clinical symptoms in patients with Fabry disease. 25‐hydroxyvitamin D (25[OH]D) was measured in 111 patients who were genetically proven to have Fabry disease. LV mass and cardiomyopathy were assessed by magnetic resonance imaging and echocardiography. In cross‐sectional analyses, associations with adverse clinical outcomes were determined by linear and binary logistic regression analyses, respectively, and were adjusted for age, sex, BMI and season. Patients had a mean age of 40 ± 13 years (42 % males), and a mean 25(OH)D of 23.5 ± 11.4 ng/ml. Those with overt vitamin D deficiency (25[OH]D ≤ 15 ng/ml) had an adjusted six fold higher risk of cardiomyopathy, compared to those with sufficient 25(OH)D levels >30 ng/ml ( p  = 0.04). The mean LV mass was distinctively different with 170 ± 75 g in deficient, 154 ± 60 g in moderately deficient and 128 ± 58 g in vitamin D sufficient patients ( p  = 0.01). With increasing severity of vitamin D deficiency, the median levels of proteinuria increased, as well as the prevalences of depression, edema, cornea verticillata and the need for medical pain therapy. In conclusion, vitamin D deficiency was strongly associated with cardiomyopathy and adverse clinical symptoms in patients with Fabry disease. Whether vitamin D supplementation improves complications of Fabry disease, requires a randomized controlled trial.